The Behavior of Bingkuang Traders in the City of Padang in Applying Islamic Business Ethics with Moderating Personality (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2021)
The research gap in this research is when the phenomenon was discovered that in the last 3 years the land for bingkuang plantations in the city of Padang has decreased by almost one third. The state of the art of this research is by adding indicators to each variable and using sentence statement questionnaires that the authors modify in the team. Respondents in this study were the traders in the city of Padang with 101 samples. From the results of partial testing with a simple regression of Islamic business ethics (X1) and personality (X2-moderating), a positive and significant effect on trader behavior. Whereas the MRA test of Islamic business ethics has a positive and significant effect on the behavior of traders, but personality does not have a strong influence in moderating between the two.